2018
DOI: 10.1007/s11769-018-0933-y
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs and Synergies of Ecosystem Services in the Taihu Lake Basin of China

Abstract: Understanding the spatial interactions among multiple ecosystem services is crucial for ecosystem services management. Ecosystem services, including crop production, freshwater supply, aquatic production, net primary production, soil conservation, water conservation, flood regulation, forest recreation, were measured at 1-km grid scale covering the Taihu Lake Basin (TLB) of China. Our objective is to get a comprehensive understanding of the spatial distributions, trade-offs, synergies of multiple ecosystem ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 42 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…The TLB (30 • 7 19"-32 • 14 56" N, 119 • 3 1"-121 • 54 26" E) is the core area of the Yangtze River Delta, which is located in the lower portion of the Yangtze River (Figure 1). It has an area of approximately 36,900 km 2 , with a complex river network and numerous lakes, of which the river density is about 3.4 km/km 2 [53].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The TLB (30 • 7 19"-32 • 14 56" N, 119 • 3 1"-121 • 54 26" E) is the core area of the Yangtze River Delta, which is located in the lower portion of the Yangtze River (Figure 1). It has an area of approximately 36,900 km 2 , with a complex river network and numerous lakes, of which the river density is about 3.4 km/km 2 [53].…”
Section: Study Areamentioning
confidence: 99%
“…It has an area of approximately 36,900 km 2 , with a complex river network and numerous lakes, of which the river density is about 3.4 km/km 2 [53]. There are more than 200 rivers and 9 lakes with an area over 10 km 2 in the basin, whereby the Taihu Lake (2427.8 km 2 ) is the largest lake in the basin and the third largest freshwater lake in China [54]. The average elevation of the TLB is 34.4 m, and there are two types of terrains in the TLB-mountains and plains.…”
Section: Study Areamentioning
confidence: 99%
“…TLB has a lake area totaling 3160 km 2 (based on the surface area of lakes > 0.5 km 2 in area), which account for 10.7% of the basin's plain area. There are 10 lakes with an area of more than 10 square kilometers, while Taihu Lake (2427.8 km 2 ) is the largest freshwater lake in the basin and the third largest freshwater lake in China [25]. Figure 2 shows the general framework for assessing how urban expansion influenced multiple ecosystem services (ESs) in the Taihu Lake Basin from 1990 to 2010.…”
Section: Study Areamentioning
confidence: 99%
“…Relationships among regulating services are characterised by either trade-offs or synergies across the studied literature. Synergies seem to occur primarily in forested areas (Maes et al 2012, Qiu and Turner 2013, Mouchet et al 2017, Kong et al 2018); however, nutrient regulation and global climate regulation appeared to have had a substantial opposite effect in two studies (Bai et al 2011, Alamgir et al 2016) Qiao et al (2018). found that, although regulating services were generally associated in the Taihu Lake Basin (China), trade-offs also occurred between flood regulation and carbon storage/water retention 7(Qiao et al 2018).…”
mentioning
confidence: 99%